Innovative method of fabrication of complete denture for abused tissues in maxilla-A case report - Ananda Deeban Kuttuva Balasubramanian Sivaprakash Babu; Singaravel Chidambara Nathan Ahila; MuthuKumar Balasubramanium (Oral Oncology Reports)
Background: A fibrous or flabby ridge is a superficial area of soft, fleshy, mobile soft tissue which affects the alveolar ridge of maxilla or mandible. Conventional impression technique cannot be followed while making impression of flabby ridge area. Conventional acrylic denture cannot be given to individuals having flabby ridge area because hard surface of denture makes uncomfortable to the patients. Case report: A 55 year old male patient had a history of wearing a maxillary complete denture for 5 years. Denture was ill fitting and no retention were present. On intraoral examination, a completely edentulous maxillary arch with inflamed movable flabby tissue was existing in the anterior region. The management started with making diagnostic impression with alginate material and a window has been created in special tray while making a secondary impression. Then border moulding has been done followed by secondary impression. In flabby ridge area it is recorded with the help of light body addition silicone. Then jaw relation and wax try in was done. While processing the denture soft liner was used to cover flabby area which provides the cushioning effect. Conclusion: Implementation of some modifications in current impression techniques and newly introduced materials with improved physical and handling properties, flabby ridges can be treated effectively without any additional visits of patients in clinical practice.